Studying and Comparing the Problems of Using GeoGebra Application in Learning – Teaching for Mathematics Teachers at Secondary School as Classified by Gender, Work Experience and School Size - YANG, Cheng; BOUNTHONG, Bounseng; PHETHSOMBATH, Sengdao; Xang, Yang; VONGSIPASEUN, Bounmor (Souphanouvong University Journal Multidisciplinary Research and Development, 2024)
The objectives of this study were to study and compare the problems for using GeoGebra application in learning and teaching of the mathematics teacher at secondary school as classified by gender, work experience and school size in three aspects including teacher based, hardware and using software. The simple group was mathematic teachers who are studying at teacher training college, there was 78 teachers in academic year 2023-2024 by accidental sampling. The research instrument was a 5-level rating scale questionnaire. The discrimination value between 0.20 – 0.79 and the coefficient reliability was 0.935; The statistics used in the research were percentage, Mean, standard deviation, t-test, One-way ANOVA and Scheffe’s Method. The research found as follow: 1). Problems of using GeoGebra application in learning – teaching for the mathematics teacher at secondary school in overall were at a median level. When discussion each aspect found: Teacher based is at a much level, hardware and using software were at a median level. 2). Comparing the problem of using GeoGebra application in learning – teaching for the mathematics teacher at secondary school classified by gender, work experience in overall and each aspect were not significant difference at the 0.05 level. Comparing the problem of using GeoGebra application in learning – teaching for the mathematics teacher at secondary school classified by school size in overall and each aspect were significant difference at the 0.05 level.